Organizational readiness to adopt artificial intelligence in the exhibition sector in Western Europe. (August 2022) - Hradecky, David; Kennell, James; Cai, Wenjie; Davidson, Rob
Abstract: This exploratory study explores perceptions of Artificial Intelligence (AI) and organizational readiness to adopt AI, in the exhibition sector of the events industry. A theoretical framework synthesizing the Technology - Organization - Environment framework and the Technology Readiness Index was developed to guide this qualitative study. Seventeen senior managerial representatives from exhibition organizations across nine Western European countries were interviewed, and a reflexive thematic approach was adopted to analyse the data. The findings suggest that the European exhibition industry is a slow adopter of AI, which may impact its future competitiveness, despite the stimulus provided to AI adoption during the COVID-19 pandemic. The degree of confidence in organizational technological practices, financial resources, the size of the organization, and issues of data management and protection, as well as the impacts of the COVID-19 pandemic, motivate or inhibit readiness for AI adoption in the event industry. A new Exhibition Sector Readiness for AI Adoption Model is presented in this research that managers and researchers can use to analyze inhibitors and motivations for AI adoption, which is contextualized for the current challenges facing the exhibitions sector. Highlights: Artificial Intelligence (AI) offers significant benefits to the events industry. Qualitative research reveals European-wide perceptions of AI adoption in events. The exhibitions sector of the event industry is a slow adopter of AI. A new model is proposed to understand and guide AI adoption in the exhibitions sector.